Diagnostics to support elimination of lymphatic filariasis—Development of two target product profiles - Won, Kimberly Y.; Gass, Katherine; Biamonte, Marco; Dagne, Daniel Argaw; Ducker, Camilla; Hanna, Christopher; Hoerauf, Achim; Lammie, Patrick J.; Njenga, Sammy M.; Noordin, Rahmah; Ramaiah, Kapa D.; Ramzy, Reda; et al. (PLOS Neglected Tropical Diseases, 2021)
Author summary High quality diagnostic tools are an essential component of lymphatic filariasis (LF) programs. Currently, diagnostic tools are used by national programs to establish baseline endemicity, monitor progress of program interventions, determine when interventions can be stopped, and surveillance. For years, LF programs have relied on diagnostic tools that have been central to informing key program decisions but were not necessarily designed to undertake the roles for which they are used. Known limitations of existing diagnostic tools make it challenging to have confidence that program endpoints have been achieved. Target product profiles (TPP) provide product requirements to guide developers and manufacturers in their efforts to design tools fit for purpose. However, development of diagnostic tools used in public health programs requires consideration of aspects beyond those considered when developing diagnostic tools used for clinical diagnosis. The TPP process for two LF use cases brought to the forefront the importance of linking use case, program platform and diagnostic performance characteristics when defining required criteria for diagnostic tools.